Stimulating the Right Temporoparietal Junction with tDCS Decreases Deception in Moral Hypocrisy and Unfairness - Tang, Honghong; Ye, Peixia; Wang, Shun; Zhu, Ruida; Su, Song; Tong, Luqiong; Liu, Chao (Frontiers in Psychology, 2017)
Self-centered and other-regarding concerns play important roles in decisions of deception. To investigate how these two motivations affect deception in fairness related moral hypocrisy, we modulated the brain activity in the right temporoparietal junction (rTPJ), the key region for decision making involved in self-centered and other-regarding concerns. After receiving brain stimulation with transcranial direct current stimulation (tDCS), participants finished a modified dictator game. In the game, they played as proposers to make allocations between themselves and recipients and had a chance to deceive by misreporting their totals for allocations. Results show that deception in moral hypocrisy was decreased after anodal stimulation than sham and cathodal stimulation, only when participants know that their reported totals (appearing fair) would be revealed to recipients rather than being unrevealed. Anodal stimulation also increased offers to recipients than cathodal stimulation regardless of the revelation of reported totals. These findings suggest that enhancing the activity of rTPJ decreased deception caused by impression management rather than self-deception in moral hypocrisy and unfairness through facilitating other-regarding concerns and weakening nonmaterial self-centered motivations. They provide causal evidence for the role of rTPJ in both other-regarding concerns and nonmaterial self-centered motivations, shedding light on the way to decrease moral hypocrisy.